New data from old bones: A taphonomic reassessment of Early Iron Age beef ranching at Nichoria, Greece. (April 2020) - Dibble, Flint; Fallu, Daniel J.
Highlights: Chronological variance in preservation found in reanalysis of fauna from Nichoria. Sediment preserved in unwashed bone bags shows attritional soil formation. Attritional soil formation explains the increase in cattle specimens at EIA Nichoria. Similar mortality profiles from tooth wear shows method is unaffected by attrition. Similar animal management strategies rejects pastoral hypothesis at EIA Nichoria. Abstract: This paper evaluates the evidence for post-depositional attrition from faunal material and sediments from Nichoria in Southwest Greece excavated over 40 years ago. Initial publication concluded that a relative increase in cattle in the Early Iron Age settlement indicated a shift to beef ranching. Without access to original archaeological contexts, geoarchaeological analyses were conducted on intact aggregates of sediment from unwashed bags of bone. The results reveal that material underwent differential attrition, likely related to depth from surface, that affected the composition of chronologically sensitive assemblages. The increased presence of cattle in the Early Iron Age is, therefore, more likely related to differential preservation. Well-preserved Early Iron Age assemblages do not show an increased presence in cattle, and similar mortality profiles between the Late Bronze Age and Early Iron Age suggest animal management strategies remained broadly similar. These analyses demonstrate the potential for applying modern taphonomic analyses to older collections.